2019
DOI: 10.1038/s41598-019-39462-1
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Cannabis Product Characteristics and Symptom Relief

Abstract: Federal barriers and logistical challenges have hindered measurement of the real time effects from the types of cannabis products used medically by millions of patients in vivo . Between 06/06/2016 and 03/05/2018, 3,341 people completed 19,910 self- administrated cannabis sessions using the mobile device software, ReleafApp to record: type of cannabis product (dried whole natural Cannabis flower, concentrate, edible, tincture, topical), combustion method (joint, pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…This lack of information arises primarily from historical federal regulatory barriers to assessing the Cannabis plant's medicinal potential, which have largely limited investigations to cannabisderived formulates or synthetic analog therapies not widely generalizable to the vast range of common, commercially available products used by millions of people every day (National Academies of Sciences, E. and M 2017; Stith and Vigil 2016). Few studies to date attempt to measure how the broad range of cannabis products, with widely varying cannabinoid contents and ingestion methods, affect momentary symptoms of distress under naturalistic circumstances (Cuttler et al 2018;Stith et al 2019;Stith et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of information arises primarily from historical federal regulatory barriers to assessing the Cannabis plant's medicinal potential, which have largely limited investigations to cannabisderived formulates or synthetic analog therapies not widely generalizable to the vast range of common, commercially available products used by millions of people every day (National Academies of Sciences, E. and M 2017; Stith and Vigil 2016). Few studies to date attempt to measure how the broad range of cannabis products, with widely varying cannabinoid contents and ingestion methods, affect momentary symptoms of distress under naturalistic circumstances (Cuttler et al 2018;Stith et al 2019;Stith et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes are known as early adopters of new and innovative modalities to aid in recovery and performance (Conrad et al 2019;Caine et al 2012), particularly since pain, insomnia, and anxiety are common and difficult to solve problems among athletes (Hainline et al 2017;Mann et al 2007;Halson 2014). Cannabis is a modality that has reportedly improved symptoms among sufferers of pain, insomnia, and anxiety (Stith et al 2019;Mannucci et al 2017), but has rarely been studied in the context of adult athlete use. Historically, cannabis use in athletes has typically been studied in the framework of abuse among adolescent, university, and elite athletes (Ware et al 2018;Buckman et al 2011;Peretti-Watel et al 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of use are related to subjective effects to cannabis (Daniulaityte et al 2018;Ware et al 2005). Frequency of use, route of administration, and type of cannabinoid used all impact the effects to cannabis (Stith et al 2019;Sexton et al 2016;Stith et al 2018). A comprehensive study of medical cannabis patients found that the primary route of administration was inhalation (84%); oral administration was only 8, and 0.6% used topicals (Peretti-Watel et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are no data on the dose, type, and mode of cannabis consumption. Stith et al used mobile device software to collect data from 3341 cannabis users affected with several diseases [21]. The main outcome was the change in symptom severity, as reported by the patient.…”
mentioning
confidence: 99%